«HYBRID WAR» OF NOTIONS - O. Fridman (Vestnik MGIMO-Universiteta)
Ofer Fridman holds the degrees of BA (Military History and Security Studies) from Hebrew University, MA (Counter-Terror and Homeland Security) from Interdisciplinary Center Herzliya and PhD (Political Science, supervised by Prof. Beatrice Heuser) from University of Reading. He is a Sessional Lecture at the University of Reading and was a Visiting Research Fellow and Visiting Lecturer at the Moscow State Institute of International Relations (MGIMO) in 2014. Ofer joined the War Studies Department at King's to conduct a research project that focuses on the politicisation of'Hybrid Warfare'. During his visit of Moscow to conduct a quantitative research of Russian military research publications "MGIMO Review of International Relations" took the following interview from him.